BELAJAR LITERASI LINGKUNGAN DARI JEPANG DALAM UPAYA MENINGKATKAN KESADARAN MASYARAKAT MENJAGA LINGKUNGAN PADA MASA PANDEMI COVID-19 - Eli Syarifah Aeni (Abdimas Siliwangi, 2022)
The environment is an area or area and so on that affects the growth of humans and animals. Environmental literacy is a person's ability to understand and interpret environmental conditions. If it is related to environmental literacy, it means someone who is literate / cares about their environment. Through his knowledge of environmental literacy, it is hoped that a person can decide on the right action to maintain, restore, and improve good environmental conditions, especially in conditions during the current pandemic. Japan is a country that has a very good level of environmental literacy. Protecting the environment is the obligation of all parties, including in Japan, the habit of protecting the environment has been taught to children since they were at the elementary school level. The purpose of cultivating environmental literacy as a character is to instill a high sense of concern for the existence of the environment and to prepare environmentally conscious people. By doing so, it is hoped that many environmental problems that have been occurring can be resolved. During the Covid-19 pandemic like this, protecting the environment and instilling awareness of the importance of cleanliness, order and protecting the environment are the most important things. As a result of the Covid-19 pandemic, it has awakened all people, from the smallest family environment, society, educational environment, to people in various parts of the world to care more about their environment. Indirectly, this incident has reminded humans to always protect their environment from various damages and pollution that cause harm to nature. We can see high environmental literacy skills in Japanese people who have very good awareness in protecting their environment. Environmental literacy is closely related to a person's character, attitude and behavior towards their environment. Through this service, researchers not only invite, but directly see and practice what environmental literacy has been done by the Japanese state. This is where the role of the community is directly involved in maintaining, caring for, and getting used to healthy living through a well-maintained and clean environment.